Plantas de cobertura em pré-safra e adubação nitrogenada na fertilidade do solo em diferentes camadas, cultivado com milho em sistema de plantio direto e convencional - Andrioli, Itamar [UNESP]; Prado, Renato de Mello [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The species of cover crops in pre-harvest of maize crop may influence the soil chemical properties. The objective was to evaluate soil fertility due to the use of plant species cover, previously cultivated with maize crop in no-tillage and conventional and subjected to nitrogen. The experiment was conducted at UNESP in Jaboticabal-SP, in an Oxisol clay during the crop years 2000/01, 2001/02 and 2002/03. The experimental design was randomized blocks in split plots with four replications. The treatments consisted of nitrogen (0, 60 and 120 kg N ha(-1)) and planting systems, and three under no-tillage system with the use of cover crops: Brachiaria, millet, Crotalaria and lablab, and under a conventional tillage. We evaluated at the flowering stage of corn, covering the crop year 2002-2003, the chemical soil layers (0-0.05, 0.05-0.10, 0.10-0.20; 0.20-0.30 m deep). Tillage systems and nitrogen levels influenced differently to the chemical properties of soil layers studied. Regardless of the nitrogen used in the conventional treatment showed lower organic matter content, calcium and value of sum of bases in the topsoil.
Cover plants in pre-harvest and nitrogen in soil fertility in different layers with corn in no tillage and conventional system
Keywords: Zea mays; green manure; crop succession; chemical attributes (0-0,05m)